The Impact of Climate Change on Mental Health: A Systematic Descriptive Review - Cianconi, Paolo; Betrò, Sophia; Janiri, Luigi (Frontiers in Psychiatry, 2020)
Abstract Background Climate change is one of the great challenges of our time. The effects in terms of consequences of climate change on exposed biological subjects and on most vulnerable societies are a concern of the whole scientific community. Rising temperatures, heat waves, floods, tornadoes, hurricanes, droughts, fires, loss of forest and ice, disappearance of rivers, advancement of desert can cause both directly and indirectly human pathologies that are both physical and mental. Psychiatric studies about mental disorders linked to climate change are very scarce. Methods We reviewed all papers available on Pubmed, EMBASE and Cochrane library from February 2018 to the end of June 2019. Articles and association reports were 212, out of which 117 were selected. We looked for the association between classical psychiatric disorders such as anxiety schizophrenia, mood disorder and depression, suicide, aggressive behaviors, despair for the loss of usual landscape, and phenomena related to climate change and weather extreme events. Results Climate impacts expose more people in more places to public health threats. However, some delay in studies on climate change and mental health consequences is to be highlighted, due to the complexity and novelty of the matter. It has been shown that climate change acts on mental health with different timing. The phenomenology of the effects of climate change is different: some mental disorders are common and others more specific because of peculiar climatic conditions. Climate change also affects different population groups that are directly exposed and more vulnerable in their geographical conditions, access to resources, information and protection. It is worth underlining that in some paper the association between climatic events and mental disorders was described through the introduction of new terms (ecoanxiety, ecoguilt, ecopsychology, ecological grief, solastalgia). Conclusions The effects of climate change can be either direct or indirect, on a short- or long-term basis. Acute events are able to act through the mechanisms of traumatic stress, leading to well known psychopathological patterns. Beyond that, the consequences of exposure to extreme or prolonged weather events may be delayed, encompassing disorders other than posttraumatic stress, or even transmitted in subsequent generations.